Authentic Assessment Competence of Building Construction Teachers in Indonesian Vocational Schools - Hadi Prayitno, Sutarto; M.P.D., & Jaedun (Journal of Technical Education and Training, 2018)
In the year 2020-2035 the number of productive citizen (15-60 years) of Indonesia will reach 70 percent over all citizens. It becomes a bonus when the citizen group possesses competence relevant to the era. Entering 21st century most important skills that a worker needs to acquire are: collaboration, creativity and problem-solving and character qualities like persistence, curiosity and initiative. In response to this issue, in 2013 Ministry of Education and Culture developed a new curriculum called â€œ2013 Curriculumâ€. It emphasises on authentic-learning and assessment that promote higher-order thinking skills: creative, innovative, and problem solving in real life. This research focuses on teachersâ€™ authentic assessment competence at the state vocational schools describing their understanding on the concepts and principles of authentic assessment and their ability in its planning and implementation. The findings show that teachersâ€™ understanding and their ability to plan and implement authentic assessment are inadequate and furher training on authentic assessment is recommended.